An equivalent plane strain model of PVD-improved soft deposit. (November 2018) - Nguyen, Ba-Phu; Yun, Dae-Ho; Kim, Yun-Tae
Abstract: An equivalent plane strain model of prefabricated vertical drain (PVD)-improved ground was simply proposed. In this study, an equivalent horizontal permeability was obtained from the matching of the total volume of water to be discharged in an axisymmetric model and the total changes in flow in a plane strain, while the geometry of the drains was deduced from the balancing of the area ratio. The effects of the smear zone and well resistance were also considered in proposed model. The verification was implemented and analyzed results of proposed method were in good agreement with observed results for two case histories.